Mitochondrial BKCa channel - Balderas, Enrique; Zhang, Jin; Stefani, Enrico; Toro, Ligia (Frontiers in Physiology, 2015)
Since its discovery in a glioma cell line 15 years ago, mitochondrial BKCa channel (mitoBKCa) has been studied in brain cells and cardiomyocytes sharing general biophysical properties such as high K+ conductance (~300 pS), voltage-dependency and Ca2+-sensitivity. Main advances in deciphering the molecular composition of mitoBKCa have included establishing that it is encoded by the Kcnma1 gene, that a C-terminal splice insert confers mitoBKCa ability to be targeted to cardiac mitochondria, and evidence for its potential coassembly with β subunits. Notoriously, β1 subunit directly interacts with cytochrome c oxidase and mitoBKCa can be modulated by substrates of the respiratory chain. mitoBKCa channel has a central role in protecting the heart from ischemia, where pharmacological activation of the channel impacts the generation of reactive oxygen species and mitochondrial Ca2+ preventing cell death likely by impeding uncontrolled opening of the mitochondrial transition pore. Supporting this view, inhibition of mitoBKCa with Iberiotoxin, enhances cytochrome c release from glioma mitochondria. Many tantalizing questions remain. Some of them are: how is mitoBKCa coupled to the respiratory chain? Does mitoBKCa play non-conduction roles in mitochondria physiology? Which are the functional partners of mitoBKCa? What are the roles of mitoBKCa in other cell types? Answers to these questions are essential to define the impact of mitoBKCa channel in mitochondria biology and disease.